FRUIT BATS DIVERSITY IN THE THREE SITES IN ARGAO WATERSHED,SOUTHERN CEBU, PHILIPPINES - Alcazar, Steve Michael T; Agbay, Eva A; Lillo, Edgardo P; Malaki, Archiebald B; Alburo, Hemres M; Obiso, Leslie S; Hoyohoy, Glenn B; Rica, Rachel Luz V; Manalastas, Rebecca C; Opiniano, Rosalyn P (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
Field surveys were conducted at the three sites in Argao watershed between 2004 December to 2005 April. This watershed is covered by natural forest that develops in fragments. These patches of natural forests can be found in Mount Lantoy, Canbantug , and Cansuje .The bats were assessed using mist nets (1.22 m x 6 m) which were placed at different elevational gradients. A total of eight species of fruit bats were recorded across study sites. Four species were common to all sites: Cynopterus brachyotis, Macroglossus minimus, Ptenochirus jagori, a Philippine endemic, and Rousettus amplexicaudatus. Other species which is significant and of high conservation concern were also captured; namely, Nyctimene rabori, a Philippine endemic, which was captured in Canbantug, Haplonycteris fischeri, a Philippine endemic,was captured in Cansuje and Canbantug, Eonycteris spelaea was recorded in Mount Lantoy and Cansuje, and Pteropus pumilus was recorded in Mount Lantoy. The presence and low relative abundance in the study sites of three Philippine endemic species; namely, H. fischeri, P. jagori, and P. pumilus indicate considerable conservation importance to concerned agencies and local communities. Thus, the planting of tree species which are favored by foraging fruit bats and building of a forest corridor should be undertaken because these entail an effect on fruit bat species composition and relative abundance. The undisturbed natural forest should also be protected from future disturbance, since it was noted that fruit bats were using undisturbed forest far more than disturbed forest. This study was undertaken to gather information about fruit bats diversity in Mount Lantoy, Canbantug, and Cansuje, which will form part of baseline data of Argao watershed. We determined species composition and relative abundance of fruit bats in the three sites above- mentioned.